Comparison of different sucrose‐based extenders for stallion sperm vitrification in straws. (21st September 2018) - Consuegra, C.; Crespo, F.; Dorado, J.; Ortiz, I.; Diaz‐Jimenez, M.; Pereira, B.; Hidalgo, M.
Abstract: Vitrification of sperm is based on high‐speed freezing by direct exposure to liquid nitrogen using non‐permeable cryoprotectants, mainly disaccharides; yet, the concentration of cryoprotectants has a species‐specific effect on the sperm cell. The aim of this study was to assess different sucrose concentrations for stallion sperm vitrification. Semen samples ( n = 9) were collected from three stallions, centrifuged and resuspended to a concentration of 50 × 10 6 sperm/ml in a base extender (INRA96 + 1% of bovine serum albumin) with three different sucrose concentrations (Molar): 20 mM (S1), 100 mM (S2), or 200 mM (S3). Then, sperm were filled in covered 0.25 ml straws and directly plunged into liquid nitrogen. For warming, 0.25 ml straw was pulled out the covering straw and immersed in 3 ml of INRA96 at 43°C, with gentle pipetting to accelerate the melting. Total (TM, %) and progressive sperm motility (PM, %) were analysed using computer‐assisted sperm analysis. Plasma (PMI, %) and acrosome membrane integrity (AIS, %) were assessed under epifluorescence microscopy. Post‐warmed sperm parameters were compared between treatments by ANOVA. S2 showed significantly higher values in comparison with S1 and S3 for TM (S2 = 54.7 ± 5.5 a ; S1 = 29.1 ± 3.3 b ; S3 = 28.6 ± 3.0 b ; p < 0.001) and PM (S2 = 31.3 ± 3.8 a ; S1 = 18.5 ± 2.6 b ; S3 = 17.7 ± 2.9 b ; p < 0.01), respectively. No significant differences were found among treatments for PMI (S2 = 70.3 ± 5.2; S1 = 67.4 ± 4.3; S3 = 70.0 ± 3.7) neither for AIS (S2 = 57.1 ± 3.9; S1 = 53.9 ± 4.2; S3 = 57.0 ± 7.9). In conclusion, a concentration of 100 mM sucrose is recommended for stallion sperm vitrification in straws.